Factors Influencing Purchase Intention Of Water Purifier In Malaysia - Wong CheeHoo, SengTeck Tan, Alex Hou Hong Ng, ToongHai Sam, Tan Wai Sung, Alvin LiauChee How (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The water purifier has become a necessity in every household these days due to accessing to clean water is a vital for everyone health. The water purifier companies are facing intense competition and thus, it is very difficult for the companies to maintain an advantageous position by offering good products at a reasonable price and with consumer-centric in mind. They have to better understand on purchase intention of consumers to be able to reap better profits. This research aimed to understand the purchase intention of consumers on water purifier in Malaysia. In this paper, four factors influencing purchase intention of consumers had been examined based on Theory of Planned Behaviour (TPB). The data on purchase intentions on water purifier had been collected through an online survey in Malaysia. Data were successfully collected from 200 respondents and was analysed descriptively. For hypotheses testing, it was tested by using SPSS-regression analysis. The results showed that consumers were influenced by the factors of conveniences, security, social influence and speed. This study suggested that for the company to be more competitive in the market, these factors should be taken into consideration in enhancing their business performance.